Structural change in the Mozambique economy between 2007 and 2019: A social accounting matrix approach - Dirk van Seventer; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This study makes use of Mozambican social accounting matrices (SAMs) for the years 2007 and 2019, which we compare to uncover structural changes. Our findings reflect the significant short- and long-term challenges that Mozambican policy makers face. Broad-based dynamic change and structural transformation is lacking. Using structural decomposition analysis, the study finds that at the economy-wide level, final demand is the overwhelming determinant of the change in value added. The change in the final demand expenditure patterns and the shift between domestic and foreign final demand had little impact over the period of observation. The change in adding value per unit of gross output made a negative contribution to the overall change in value added. On average, industries became less adept at adding value to their intermediate inputs. On the other hand, a positive impact of the technology effect was found in that sectors shifted backward linkages such that this added to change in value added, although the effect is relatively small. This is confirmed in that the value added multipliers declined over the period whereas those of gross value of production remained more or less the same.
Keywords: D31; D33; D57; E16; J21; 330; social accounting matrix; national accounts; structural change; economic shocks; income distribution; Mozambique